Bridging the politico-administrative divide - Giacchino, Stephen (Cranfield University, 2003)
This thesis presents the findings and conclusions of research that was undertaken with the purpose of exploring the issues (or factors) that typically influence the successful, or unsuccessful, implementation of public policy initiatives in Malta. The research, which followed an inductive enquiry and a case study approach, was undertaken in three sequential and progressive steps (or ‘projects’). The objective of Projects 1 and 2 was to elicit the factors that are typically considered to influence failure and success in the implementation of policy initiatives in Malta. While Project 1 focused on a case study of failure, Project 2 considered a case study of successful policy implementation1. Both studies were based upon data collected through documentary research (172 records)2 and in-depth interviews (17)3 that were held with the key persons involved in the implementation of the policies under review. Twenty-six (26) factors of failure and twenty-one (21) factors of success were identified through the application of cognitive (causal) mapping techniques (Eden, Ackermann et al., 1992) and the general principles of data codification proposed by Strauss and Corbin (1998). Using a survey of 136 persons4, Project 3 then established which of the factors elicited from the first two projects were generally considered to be critical for policy implementation in Malta. Focusing on these results, a number of propositions were then drawn with the objective of recommending measures that would improve the likelihood of successful policy implementation. The research concludes that the decisive factors influencing the successful or unsuccessful outcome of policy implementation in Malta are a function of the type and degree of commitment and leadership that are shown to a policy initiative. The research further suggests that success can be improved if the approach to the management of policies is based on the application of the principles of project management. The research makes a number of contributions to both theory and practice. Most notably, it proposes two conceptual models for framing and representing success and failure in policy implementation; it ascribes meaning to a number of clichéd concepts, particularly that of ‘(policy) commitment’; it identifies eight dimensions or requisites for effective (public sector) leadership; and it suggests a tool for guiding the selection of policy implementation leaders.